Internal governance and creditor governance: Evidence from credit default swaps - Stefano Colonnello (Leibniz-Institut für Wirtschaftsforschung Halle (IWH), 2017)
I study the relation between internal governance and creditor governance. A deterioration in creditor governance may increase the agency costs of debt and managerial opportunism at the expense of shareholders. I exploit the introduction of credit default swaps (CDS) as a negative shock to creditor governance. I provide evidence consistent with shareholders pushing for a substitution effect between internal governance and creditor governance. Following CDS introduction, CDS firms reduce managerial risk-taking incentives relative to other firms. At the same time, after the start of CDS trading, CDS firms increase managerial wealth-performance sensitivity, board independence, and CEO turnover performance-sensitivity relative to other firms.
urn:nbn:de:gbv:3:2-68392
Keywords: G32; G34; 330; creditor governance; credit default swaps; empty creditors